Framing the concept and practice of cultural governance in the Philippines from multiple lenses - Salazar, Gina S. (National College of Public Administration and Governance, University of the Philippines Diliman, 2019)
The study formulates the concept and practice of cultural governance in the Philippines from the viewpoint of the National Commission for Culture and the Arts, National Commission on Indigenous Peoples, Local Government Unit (LGU) of the City of Malolos, LGU of Norzagaray, the community-based artists groups of the City of Malolos, and Dumagats of Norzagaray. Using a modified version of Powell's Mixed Methods Multiple Case Study Framework as research design, data gathered through interviews, focus group discussions, and surveys are analyzed at within-case and cross-case levels through qualitative analysis (inclusive of document review) and quantitative analysis using Multivariate Analysis of Variance and Computed Median. The analysis has established that cultural governance in the Philippines is highly cultural more than it is ideological, sectoral or economic. Having culture in governance in as the dominant and convergent sense among the cultural sectors in the national, local and community levels of cultural governance manifests the importance attributed to the intrinsic and instrumental values of culture. The divergent senses, which express that culture is independent of governance; culture must support governance; and cultural governance is a cycle of Governance for Culture and Culture for Governance, suggest that culture is the broader context of the process of cultural governance, and that the divergent senses remain to be aligned with the dominant and convergent sense in attributing culture the power of influence over the process of cultural governance. The priority components are found to be funding and policy or legislation, with cultural projects, identified as either low culture or high culture, as the default significant component. It is established that the level of importance attributed to cultural projects is not in any way influenced by the low culture or high culture nature of cultural activities. The prioritization of the cultural sectors is the promotion of the preservation of culture through capacity building, empowerment, and livelihood cultural projects. This is not the expected priority given GIG as the dominant and convergent sense, but it remains to be expressive of the recognition that culture is the core of cultural governance. The cultural sectors' understanding of how culture affects life and development constitutes their philosophy of cultural governance. The legal frameworks for the practice of cultural governance, with the exception of Customary Laws of the IPs, are well-established only at the level of the NGAs. The three basic institutional mechanisms correspond to the three significant components of cultural governance: budgeting for funding, law-making for legislation, and administrative mechanisms for the implementation of cultural projects. Philippine cultural sectors are fully aware of how to plan their cultural programs based on their mandates and prioritizations as they are confronted with the arduous task of resolving issues rooted in the commitment to and mindset about culture.From the aforementioned as features, the Philippine Cultural Governance model is constructed.